Need analysis of English for Hospitality students: A case study in Sungai Petani Community College - Gopal, Krishnavehni; Quah, Wei Boon; Gengatharan, Sasikumar (AJELP: Asian Journal of English Language and Pedagogy, 2021)
Malaysia, as a rapidly developing nation, plays a crucial role in equipping its graduates with all the necessary skills which are considered highly in demand in the current market. Course designers need to consider the target learning needs of ESP students in redesigning an appropriate syllabus that will cater to their working needs. Needs analysis is a way of determining and outlining syllabus and teaching methods to achieve a valuable learning environment. Instructors and teachers conducting English classes ought to identify their students’ needs to build an appropriate curriculum that facilitates a better learning process. Therefore, the objective of this study is to identify the English Language needs of Community College English for Hospitality students. 40 internship Hospitality students from a Community College, and 40 industry personnel participated in this study. All these participants were from Malaysia. The questionnaires were used as the main instruments in this study. The finding shows that 62.5% of the respondents’ main reason for learning English is to improve their speaking skills as they are mainly dealing with answering telephone calls, inquiries on hotel facilities as well as handling hotel reservations. The finding further reveals that major emphasis should be given to listening and speaking skills as they are more widely used when dealing with the guests. It is hoped that the findings of this study are used to propose an English for Specific Purposes syllabus, which would benefit future hospitality students in public or private colleges.